Analysis of Inaccuracy in Social Assistance Recipients: A Literature Study on the Effectiveness of Government Programs - Muhammad Aras Prabowo; Tasya Rahma Dita; Vita Febria Mutia Zein (Trescode Green Organization, 2025)
This study highlights the issue of inaccuracies in the distribution of Social Assistance (Bansos) in Indonesia during the COVID-19 pandemic, emphasizing the factors that contribute to the misallocation of aid. From the literature analysis, it was found that the main errors lie in inaccurate recipient data and a lack of coordination between government agencies. The failure to update data regularly has led to aid being given to individuals who no longer meet the criteria, while those who genuinely need it are overlooked. The politicization of Bansos distribution is also a significant factor, where aid is often used as a political tool, leading to inequities in its distribution. A weak verification system further exacerbates this situation. This study recommends regular data updates, improved coordination between agencies, and the use of information technology to enhance the accuracy of Bansos distribution. Community involvement in the distribution process and monitoring of aid is also considered crucial to ensure that Bansos reaches those who truly need it. These findings provide guidance on improving the effectiveness and fairness of the Bansos program in Indonesia, which is expected to have a positive impact on the welfare of communities affected by the pandemic.